HUBUNGAN KETERPAPARAN MEDIA MASSA INTERNET DENGAN USIA MENARCHE PADA SISWI DENGAN STATUS GIZI LEBIH DI SMP NEGERI KECAMATAN PAUH KOTA PADANG TAHUN 2020 (JURNAL KESEHATAN MERCUSUAR, 2020)
ABSTRACTIn the last decade the age of menarche has shifted to a younger age. The age of the youngest menarche in Indonesia is 9 years with a prevalence of 15.3%. West Sumatera, 41,4% of young woman experience interest at the age of 13-4 years. Girls who experience menarche early are at risk of experiencing malignant disease, including cancer. Excessive nutrition and media exposure are factors that trigger early menarche. A preliminary survey of 10 respondents found that the age of early menarche was 6 students. out of 6, the internet media exposure was 2 people and 4 weight. The purpose of this study was to determine the relationship of internet mass media exposure to the age of menarche in female students with over nutritional status in State Junior High School, Pauh District, Padang City in 2020. This type of research is quantitative, analytic survey with cross sectional design.  The study population was all female students with more nutritional status at SMPN 23 Padang and SMPN 14 Padang, Pauh District, Padang City with total sampling techniques, which fulfilled the sample questionnaire of 52 respondents. Then the data were analyzed univariately and bivariately with the Chi-Square statistical test. The results showed that 53.8% of respondents had exposure to heavy internet mass media, and 63.5% of respondents experienced early menarche age.  The youngest menarche age is 10 years and the oldest is 14 years 7 months. The average age of menarche is 11.4 years. The relationship of internet mass media exposure with the age of menarche in students with more nutritional status with a p value of 0.027 (p
Keywords: Usia Menarche, Keterpaparan Media Massa Internet, Status Gizi Lebih